Contrecoup Injury associated with Fatal Portal Vein Bleeding: A Case Report - Joonghyun Yoo (The Korean Society of Radiology, 2021)
A 64-year-old male visited our emergency department due to severe right flank pain after falling from a 2-meter height. Contrast-enhanced CT revealed a right hemothorax with multiple fractures in the right ribs and iliac bone. A small hematoma in the right perihepatic space was noted, but there was no hepatic laceration on CT. Initial surgical management led to continuous uncontrolled bleeding around the porta hepatis, and subsequent arterial angiography could not demonstrate a bleeding focus. However, immediate follow-up CT showed contrast extravasation on the left side of abdomen, and a percutaneous transhepatic portal venogram revealed active bleeding from the left portal vein. Although the wound was embolized with a glue, the patient suffered from a cardiac arrest and finally expired. In conclusion, during evaluation of abdominal trauma patients, portal vein bleeding and contrecoup injuries should be considered when hepatic arteriography findings are unremarkable.